Konflikt polityczny z perspektywy teorii zachowania zasobów - Kuświk, Justyna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
This paper analyzes the phenomenon of political conflict from the point of view of Stevan. E. Hobfoll’s Conservation of Resources theory. The first part is devoted to considerations on the principal sources of political conflict and the general pattern of its course in view of selected theories from political science and psychology. It presents the mechanisms of both cognitive and emotional functioning of individuals and groups in a conflict situation. The second part reviews the basic assumptions of the Conservation of Resources theory. This encompasses considerations on the resources that are politically significant, their definitions, and conclusions on the management of political resources. First and foremost, the analysis concerns the functions of conflict which may constitute a source of both an increase in, and loss of resources; additionally, conflict as such can also be perceived and treated as a kind of resource. The paper presents examples of political events in the 19th and 20th centuries.